Effect of graphene oxide on poly (methyl methacrylate)-grafted natural rubber polymer electrolytes / Mohammad Izzat Jaafar ... [et al.] - Jaafar, Mohammad Izzat; Raghali, Nur Firza Syazni; Syed Ismail, Sharifah Nafisah; Rajmi, Rozilah; Muhd Zailani, Nabilah Akemal; Zainal Abidin, Siti Zafirah; Nazir, Khuzaimah (Research Management Institute (RMI), 2023)
Polymer electrolytes (PE) are presently the subject of the majority of research due to their capacity to replace liquid electrolyte that suffer from high flammability and electrolyte leakage and also as a new forms of electrical power production and storage systems. Solid polymer electrolytes (SPE) typically have low ionic conductivity at room temperature because of the high crystallinity of the polymers. Methyl-grafted natural rubber has been studied extensively by a number of researchers due to its advantageous properties such as high flexibility, and ability to solvate inorganic salts to form a polymer-salt complex. Graphene oxide (GO) was used as a nanofiller, ammonium triflate (NH4CF3SO3) served as a dopant salt, and 30 % polymethyl methacrylate grafted natural rubber (MG30) served as the polymer host in the preparation of the nanocomposite polymer electrolyte (CPE) using the solution casting-method. Electrochemical impedance spectroscopy (EIS) was used to analyse the ionic conductivity of the samples, and Fourier-transform infrared spectroscopy (FTIR) was used to analyse the complexation between salt, polymer host and filler while Optical microscope was used to study the surface morphology of the prepared CPE samples. The decrease in peak strength for C=O in the FTIR spectra indicates the interaction between the polymer host and salt.